Lighting systems, current situation and perspectives - Saavedra, Enrique (2016)
Rising electricity prices, concerns about climate change, independence and energy security drive the shift from the global lighting market to more energy-efficient light sources. Lighting, according to estimates by the International Energy Agency (IEA), accounts for almost 20% of the world's electricity consumption. In Peru, according to the Ministry of Energy and Mines, approximately 35% of primary energy (after processing and / or discounting losses) is destined to electricity generation, which presents important consumption in lighting: Residential Sector 15 % to 30%, Commercial sector approx. 33%, Public sector approx. 24% and industrial sector 10% to 15%. Given these important levels of consumption in lighting systems, transverse use in all sectors, the lack of a comprehensive regulatory policy framework, as well as the need to determine and establish energy efficiency alternatives, it is necessary to know the current situation and The prospects of lighting systems. o achieve energy savings in lighting, the IEA recommends to governments: Progressive elimination of inefficient lighting products; Adopt quality lighting, reliability and minimum Energy Efficiency Standards (MEPS); Support the development, use and updating of international testing standards and measurement protocols to reduce compliance costs and support national policy requirements; Demand and promote better design and management of lighting systems by ensuring that building codes promote the use of natural light and include MEPS for lighting systems, including information and training for architects, builders, owners and managers. Currently the market is dominated by conventional lighting technologies, which are being displaced by Solid State Lighting (SSL) technology. Worldwide, SSL comprising LED, OLED and the management of lighting systems, mark the trend with great probability to achieve the goals of energy saving and efficiency. The SSL offers improved controllability, new form factors (which facilitate the replacement of conventional technologies) and new functionalities (base of the intelligent lighting industry) that can be integrated with sensor and control systems, allowing greater savings of Energy. However, the existence of more efficient technologies and light characteristics, there are barriers to its adoption, mainly: lack of information and sensitivity, lack of confidence, greater initial cost, inadequate incentives, perceived fears related to health and the environment. Also, there are a number of barriers to adoption of SSL products, these mainly include initial costs, reliability, color stability and compatibility; Which may limit adoption.